Locating the tragus based on the visibility of the outer ear in face photographs - Husin, Nor Hadhirah Che (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
Human remain in which the ante-mortem face photographs of suspected victims are overlaid on the image of the skull from the skeletal remains for establishing identity. Two important criteria for the success of superimposition method are 'life size' enlargement of face photograph and orienting the skull in the same posture as the face appears in the questioned face photograph. Positioning the skull uses two important homologous points, which are located in the two different planes in the face photograph: they are the lateral angle of the eye in front plane and the center of auditory meatus as indicated by the tragus in the ear in the rear plane. Tragus may or may not be seen in front view face photograph. Thus, when the tragus is not visible, i.e. masked by hair, the location of the tragus becomes a problem. In such instances, the forward-backward tilt in the face cannot be estimated and applied to the skull while orienting the skull. This dissertation presents the studies undertaken among 110 male subjects to estimate the location of the tragus when the tragus itself is not visible and the other parts of the outer ear such as the upper helix or the lobe is visible. The proportionate location of the tragus from the superaurale as well as subaurale was calculated and the range between was arrived at. The superaurale- tragus distance ranges between 33 to 46 mm (mean 40 mm) for the right ear and 33 to 47 mm (mean 39 mm) for the left ear. The subaurale-tragus distance ranges between 21 to 37 mm (mean 27.6 mm) for the right ear and 21 to 35 mm (mean 27.6 mm) for the left ear. The lower boundary (subaurale) is found to be better visible compared to the upper boundary (superaurale) in the samples studied here.